2016
DOI: 10.11607/ofph.1526
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with Life in Orofacial Pain Disorders: Associations and Theoretical Implications

Abstract: Aims To test if patients with masticatory myofascial pain, local myalgia, centrally mediated myalgia, disc displacement, capsulitis/synovitis, or continuous neuropathic pain differed in self-reported satisfaction with life. The study also tested if satisfaction with life was similarly predicted by measures of physical, emotional, and social functioning across disorders. Methods Satisfaction with life, fatigue, affective distress, social support, and pain data were extracted from the medical records of 343 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…Most of these have found that patients with muscle disorders have significantly higher depression scores (Manfredini et al, 2009; Park et al, 2010; Kim et al, 2012; Klasser et al, 2014; Boggero et al, 2016). Klasser et al (2014) showed that patients with myogenous TMD more often reported not only depression, but also anxiety, psychiatric treatment, phobias and severe headaches than arthrogenous TMD.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these have found that patients with muscle disorders have significantly higher depression scores (Manfredini et al, 2009; Park et al, 2010; Kim et al, 2012; Klasser et al, 2014; Boggero et al, 2016). Klasser et al (2014) showed that patients with myogenous TMD more often reported not only depression, but also anxiety, psychiatric treatment, phobias and severe headaches than arthrogenous TMD.…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate previous research that failed to find associations between trait psychological variables and PPT or pain inhibition (Geisser, Gaskin, Robinson, & Greene, ; Giesecke et al, ; Goodin et al, , ; Lautenbacher, Spernal, Schreiber, & Krieg, ; Nahman‐Averbuch et al, ). Although trait SR may be an important consideration for how people manage functioning and maintain well‐being in the face of pain (Boggero, Rojas, Carlson, & de Leeuw, ; Solberg Nes et al, ), it may not influence how sensitive people are to pain or how well they can inhibit it.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, living with a chronic pain condition requires more than merely managing pain—it requires maintaining social, occupational, and recreational functioning despite pain (Amtmann et al, ; Solberg Nes et al, ). Such persistence likely draws on regulatory resources (Boggero, Rojas, et al, ; Boggero, Rojas Ramirez, & Carlson, ). Thus, the chronic SR fatigue observed in chronic pain may not be due to pain in and of itself but rather to the cumulative effects of persisting in the face of pain, explaining why effects are seen in chronic pain but not in pain‐free samples.…”
Section: Discussionmentioning
confidence: 99%
“…Higher scores indicated higher levels of the measured construct. The MFSI-SF has been validated in patients with chronic illnesses generally and orofacial pain specifically [4-5, 19-20]. Reliability was adequate for the total score (α = .91) and for all subscales, ranging from α = .88 for physical fatigue to α = .95 for general fatigue.…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores represented higher pain interference. The WHYMPI pain interference scale has been well-validated in chronic pain samples [5, 12, 13, 19, 21]. The dataset used for the current study contained only scale scores and not individual items; as such, Cronbach’s alpha could not be computed.…”
Section: Methodsmentioning
confidence: 99%